Sistem Informasi Tata Kelola Kantor Pertanahan : Penelitian - Arisman Ismail; Agus Purwanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The land office has an important role in managing agrarian data and services in Indonesia. The problem faced at the Pekalongan City Land Office is the difficulty in controlling the borrowing of land books by staff for certain processes that are still carried out manually or in excel, so that when there is a need for the land book, its whereabouts are difficult to track. This study aims to design and create a land office governance information system called